Making conservation research more relevant for conservation practitioners - Laurance, William F.; Koster, Harko; Grooten, Monique; Anderson, Anthony B.; Zuidema, Pieter A.; Zwick, Steve; Zagt, Roderick J.; Lynam, Antony J.; Linkie, Matthew; Anten, Niels P.R. (Biological conservation, 2012)
► Much conservation research has only limited relevance to real-world conservation. ► We identify strategies to improve the impact of research on conservation outcomes. ► Communication among conservation scientists and practitioners, especially at the beginning of research, is vital. Conservation scientists and practitioners share many of the same goals. Yet in a majority of cases, we argue, research conducted by academic conservation scientists actually makes surprisingly few direct contributions to environmental conservation. We illustrate how researchers can increase the utility and impact of their scientific findings for real-world conservation, using examples of pressing environmental challenges. These examples demonstrate some practices and principles that scientists can adopt to better assist conservation practitioners and advance specific conservation outcomes. These include (1) producing time-critical research rapidly enough to affect political outcomes; (2) attacking ‘wicked’ problems that transcend traditional scientific approaches; (3) using multidisciplinary approaches that link science with fields such as economics, sociology, and politics; and (4) communicating in a bolder, more direct manner in the public arena to advance environmental conservation. We conclude with a plea for more proactive dialogue between conservation scientists and practitioners when devising research priorities.